ANALYSIS OF FACTORS INFLUENCING THE COMPETITIVENESS OF NATIONAL COMPANIES - Siddikov, Anvarbek Mamasoliyevich (THE INNOVATION ECONOMY, 2026)
This article analyzes the main factors influencing the competitiveness of national companies. In particular, it examines the impact of internal and external environmental factors, production efficiency, innovative activity, quality of management, marketing strategy, financial stability, and investment attractiveness on the competitiveness of enterprises. The paper also develops scientific conclusions and practical recommendations for improving the performance of national companies and strengthening their competitive advantages in modern market conditions.